2016
DOI: 10.1136/bcr-2016-216854
|View full text |Cite
|
Sign up to set email alerts
|

Primary tuberculous osteomyelitis of the mandible in a 3-year-old child

Abstract: A 3-year-old girl child presented with swelling in her right lower jaw that had started 5 days previously. History revealed the child being non-immunised. Initial-evaluation revealed proptosis and bony hard swelling over the right body of the mandible. Radiological evaluation including a CT scan indicated expansile osteolytic lesion involving the body-ramus with onion-peel periosteal reaction suggesting osteomyelitis/malignancy. Blood investigations showed raised erythrocyte sedimentation rate and eosinophilia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…Orofacial tuberculosis may be primary, or secondary to pulmonary tuberculosis. Secondary TB is more common in adults or geriatric cases, whereas primary oral TB generally affects younger patients [3]. Tuberculous osteomyelitis is uncommon and forms <2% of skeletal tuberculosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Orofacial tuberculosis may be primary, or secondary to pulmonary tuberculosis. Secondary TB is more common in adults or geriatric cases, whereas primary oral TB generally affects younger patients [3]. Tuberculous osteomyelitis is uncommon and forms <2% of skeletal tuberculosis.…”
Section: Discussionmentioning
confidence: 99%
“…TB osteomyelitis generally presents as swelling, pain, loosening of teeth and draining sinuses like a tooth abscess. Radiographic features are similar to chronic suppurative osteomyelitis i.e., diffuse radiolucency and altered trabecular pattern [1,[3][4][5]. Other maxillofacial manifestations of TB include an ulcer, granulomas, involvement of salivary glands and temporomandibular joint, and tuberculous lymphadenitis [6].…”
Section: Discussionmentioning
confidence: 99%
“…The lesions of primary orofacial tuberculosis could be the only presentation of the disease; however orofacial tuberculosis is usually associated with systemic manifestations of tuberculosis. [4] …”
Section: Discussionmentioning
confidence: 99%
“…Primary tuberculosis of the oral cavity is very rare .The mandibular localization of tuberculosis is rare and represents less than 2% of the skeletal locations [1] , [2] , [3] . The lesions of primary orofacial tuberculosis could be the only presentation of the disease; however the orofacial presentation is usually associated with systemic manifestations of tuberculosis [4] . Mandibular tuberculosis presents often a difficulty of diagnosis because of the rarity and non-specificity of clinical presentation and the absence of pathognomonic signs.…”
Section: Introductionmentioning
confidence: 99%
“…Sambyal SS et al reported various radiological features of tuberculous osteomyelitis [ 8 ]. In the present patient, CECT head and neck revealed the presence of an ill-defined osteolytic lesion involving the mandibular body, suggestive of osteomyelitis.…”
Section: Discussionmentioning
confidence: 99%